2006
DOI: 10.1521/aeap.2006.18.5.375
|View full text |Cite
|
Sign up to set email alerts
|

Using Community-Based Participatory Research to Develop an Intervention to Reduce HIV and STD Infections Among Latino Men

Abstract: Although the Latino community living in the United States has been disproportionately affected by the intersecting epidemics of HIV and sexually transmitted diseases (STDs), the development, implementation, and evaluation of HIV and STD prevention interventions designed to reduce infection among Latinos lags behind prevention efforts targeting other communities. HoMBReS: Hombres Manteniendo Bienestar y Relaciones Saludables is a sexual risk reduction intervention designed to reduce HIV and STD infection among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
83
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(84 citation statements)
references
References 19 publications
1
83
0
Order By: Relevance
“…These results suggest that outreach workers from migrant health clinics could be invaluable in reducing problem drinking among farmworkers. Research in other behavioral domains suggests that direct involvement of the farmworker community in the design and delivery of the intervention, such as the use of lay health promoters [Quandt et al, 2001;Rhodes et al, 2006] may be useful in reducing heavy drinking among immigrant farmworkers. Regardless of the approach taken, cultural sensitivity in the design and implementation of the intervention will play a vital role in success.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that outreach workers from migrant health clinics could be invaluable in reducing problem drinking among farmworkers. Research in other behavioral domains suggests that direct involvement of the farmworker community in the design and delivery of the intervention, such as the use of lay health promoters [Quandt et al, 2001;Rhodes et al, 2006] may be useful in reducing heavy drinking among immigrant farmworkers. Regardless of the approach taken, cultural sensitivity in the design and implementation of the intervention will play a vital role in success.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] An orientation to research, rather than a particular research method, CBPR is concisely defined as "systematic inquiry, with the participation of those affected by the problem, for the purposes of education and action or effecting change". 7 Unlike most investigatordriven approaches, CBPR emphasizes equitable engagement of all partners throughout the research process, from problem definition through data collection and analysis, to dissemination and use of findings to help effect change.…”
Section: Introductionmentioning
confidence: 99%
“…21 Although studies have included African American and Latina TW in their samples, 2,15,22,23 few have assessed contextual determinants of HIV specific to these groups. 24,25 Documentation status (legal authorization to live in the United States) is sometimes mentioned as a limitation for recruiting or retaining immigrant (noncitizen who lives in the United States) Latino/a sexual minorities in prevention and treatment, [26][27][28][29] but not as a contextual determinant of the HIV-related syndemic among transgender immigrant Latinas. For example, a prior study showed higher depressive symptoms and needs for social support among transgender Latinas compared to African Americans and Whites.…”
mentioning
confidence: 99%